THE EFFECT OF RECIPROCAL LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS X STUDENTS INFORMATICS IN PUBLIC HIGH SCHOOL 1 NGUNUT - Muhammad Akhdani Shalih; Vertika Panggayuh (STKIP PGRI TULUNGAGUNG, 2024)
This study was motivated by the low learning outcomes of students in class X SMA Negeri 1 Ngunut. The purpose of this study was to determine the effect of the application of Reciprocal Learning model on motivation and learning outcomes of informatics class X SMA Negeri 1 Ngunut. This type of research is a quasi-experiment with the design of the non-equivalent control group design. The samples of this study were taken from 2 classes X SMA Negeri 1 Ngunut. The experimental class was taught using the reciprocal learning model and the control class using the jigsaw learning model. The learning outcome test obtained showed that the average value of the experimental group was 77.60 and the average value of the control group was 65.10. Based on the hypothesis test, the sig value = 0.000 was obtained at a significant level ? = 0.05. This means that the sig value 0.05 means that the sig value is outside the H0 acceptance area. So it can be concluded that there is an effect of reciprocal learning model on the learning outcomes of class X students of SMA Negeri 1 Ngunut.